1990
DOI: 10.1021/bi00469a030
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of mixed-chain phosphatidylcholine bilayers

Abstract: The structural and thermotropic properties of the hydrated mixed-chain phosphatidylcholines (PCs), C(8):C(18)-PC and C(10):C(18)-PC, have been studied by X-ray diffraction and differential scanning calorimetry. For fully hydrated C(8):C(18)-PC, the reversible chain melting transition is observed at 9.9 degrees C (delta H = 7.3 kcal/mol). X-ray diffraction at 0 degrees C (below the chain melting transition) shows a small bilayer repeat distance, d = 51.0 A, and a sharp, symmetric wide-angle reflection at 4.1 A,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…This change in molecular packing motif results in a biphasic V-shaped profile of the experimental points in the Tm (or AH) versus AC/CL plot . This simple interpretation of the biphasic phenomenon is reasonable, since highly asymmetric phospholipids with AC/CL values of -0.55 such as C(18):C(10)PC, C(8):C(18)PC, and C(22):C(12)PC are known from x-ray diffraction studies to pack into the mixed interdigitated bilayer, in excess water, at T < Tm (Hui et al, 1984;Mattai et al, 1987;McIntosh et al, 1984;Shah et al, 1990;Zhu and Caffrey, 1993). An intriguing question still remains: Why do asymmetric phosphatidylcholines change their packing motif from a partially interdigitated to a mixed interdigitated type at a AC/CL value of -0.41?…”
Section: Introductionmentioning
confidence: 78%
“…This change in molecular packing motif results in a biphasic V-shaped profile of the experimental points in the Tm (or AH) versus AC/CL plot . This simple interpretation of the biphasic phenomenon is reasonable, since highly asymmetric phospholipids with AC/CL values of -0.55 such as C(18):C(10)PC, C(8):C(18)PC, and C(22):C(12)PC are known from x-ray diffraction studies to pack into the mixed interdigitated bilayer, in excess water, at T < Tm (Hui et al, 1984;Mattai et al, 1987;McIntosh et al, 1984;Shah et al, 1990;Zhu and Caffrey, 1993). An intriguing question still remains: Why do asymmetric phosphatidylcholines change their packing motif from a partially interdigitated to a mixed interdigitated type at a AC/CL value of -0.41?…”
Section: Introductionmentioning
confidence: 78%
“…Teflon membranes with 0.5-micron pores were obtained from Alltech (Deerfield, IL). C(18):C(2)-PC synthesis C(18):C(2)-PC had been prepared previously by Tence et al (1981), Tokumura et al (1981Tokumura et al ( , 1985, Hirth and Barner (1982), Huang et al (1984), and Shah et al (1990). We prepared C(18):C(2)-PC by a variation of the reported methods (Gupta et al, 1977;Mason et al, 1981;Mangroo and Gerber, 1988;and Ali and Bittman, 1989) for the acylation of l-acyl-snglycero-3-phosphocholines (Iyso-PC).…”
Section: Methodsmentioning
confidence: 99%
“…1-stearoyl-2-acetyl-sn-glycerol-3phosphocholine (C(18):C(2)-PC) is also structurally very asymmetrical (i.e., an 18 carbon chain at the sn-i position and a 2 carbon chain at the sn-2 position). Earlier studies on C(18):C(2)-PC (Huang et al, 1984;Shah et al, 1990) show that C(18):C(2)-PC exhibits a complicated phase behavior in contrast to lysoPC (Mattai and Shipley, 1986;Hui and Huang, 1986). Based on the DSC data, suggested that, on heating, C(18):C(2)-PC converts from a crystalline phase --gel (I) -* gel (II) -* micellar phase.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…6 in Mattai et al, 1987). Furthermore, PCs in which the length of one of its constituent chains is approximately half the length of the other seem to pack in a "mixed interdigitated" monolayer structure, in this case with the two short chains from PC molecules on each side of the bilayer being aligned against each other and the hydrocarbon width essentially being determined by the long chain (Mattai et al, 1987;McIntosh et al, 1984;Hui et al, 1984;Shah et al, 1990). In contrast to the structural studies of mixed-chain PCs, relatively little is known about the structure and properties of SM containing hydrocarbon (sphingosine and N-acyl) chains of different length.…”
Section: + -(40°c;mentioning
confidence: 99%